Delay to angiography and outcomes following presentation with high-risk, non-ST-elevation acute coronary syndromes: results from the Global Registry of Acute Coronary Events. Issue 3 (18th September 2008) - Swanson, N; Montalescot, G; Eagle, K A; Goodman, S G; Huang, W; Brieger, D; Devlin, G; ,
Abstract : Objective: To test if delay-to-angiography (>72 hours from admission) in patients presenting with high-risk non-ST-elevation acute coronary syndromes (NSTE-ACS) is associated with adverse outcomes. Design: GRACE (Global Registry of Acute Coronary Events) is a multinational registry of patients admitted with NSTE-ACS. Setting: 14 countries with varying healthcare systems. Patients: 23 396 high-risk NSTE-ACS patients with complete initial data collection entered into GRACE between 1999 and 2006 were analysed. Interventions: Data were analysed according to delay-to-angiography and subsequent in-hospital or post-discharge adverse outcomes. Main outcome measures: Outcomes recorded included death, myocardial infarction, recurrent ischaemia, stroke, new heart failure and composite major adverse cardiovascular event (MACE) comprising death, cerebrovascular accident and myocardial infarction. Revascularisation procedures were recorded. Results: 10 089 (43.1%) had no in-hospital angiography. Median delay-to-angiography was 46 hours; 3680 (34%) patients waited >72 hours. 9.3% waited >7 days before angiography. Patients waiting longest were more often older, diabetic, women and had a history of heart failure, previous myocardial infarction or hypertension. Recurrent in-hospital ischaemia (33% vs 22%), reinfarction (8.4% vs 5.0%) and heart failure (14% vs 9.1%) were more common with delayed angiography. Delayed angiography was associated with better outcomes than no angiography (MACE 18.9% vs 22.2%, p = 0.015). MACE rates within six months of admission were higher with longer delay-to-angiography and highest of all with no angiography. Conclusions: High-risk NSTE-ACS is suboptimally managed with 43% not undergoing angiography. One-third of those undergoing angiography are delayed >72 hours. Longer delays were more likely with higher risk, sicker patients. These delays were associated with adverse outcomes at six months. Very long delay was associated with lower MACE, but not mortality, compared to conservative management.